2018
DOI: 10.1111/idj.12325
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceptions and clinical application of the shortened dental arch concept among Malaysian government dentists

Abstract: Aim: To assess the knowledge and perceptions of Malaysian government dentists regarding the shortened dental arch (SDA) concept and its application in clinical practice. Background: The SDA concept refers to a specific type of dentition with intact anterior teeth and a reduction in posterior occlusal pairs. Dentists' knowledge and perceptions of the SDA concept can influence its application in clinical practice. Methods: A self-administered questionnaire on the SDA concept was distributed to 326 government den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…Improving mastication, restoring posterior support, preventing anterior tooth wear and maintaining the health of the TMJs were the main concerns for deciding to replace the missing molars. Similar concerns about the SDA concept were reported in other surveys [11, 23]. Satisfying patients' desires was also reported as a reason for providing treatment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Improving mastication, restoring posterior support, preventing anterior tooth wear and maintaining the health of the TMJs were the main concerns for deciding to replace the missing molars. Similar concerns about the SDA concept were reported in other surveys [11, 23]. Satisfying patients' desires was also reported as a reason for providing treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Other surveys reported similar results where dentists with fewer years of experience were found to be more aware of the SDA concept [11, 16, 22]. This could be a reflection of the increased incorporation of the SDA concept in undergraduate teaching in the recent years [23].…”
Section: Discussionmentioning
confidence: 65%
“…The dentist should have a positive attitude and favorable perception of it to apply it in that particular situation. In our study, similar to the previous studies [22], [30], [32], participants showed positive attitudes toward SDA in various clinical situations, as shown in Table 3. This result supports the fact that the ultimate success of the treatment is determined by a good long-term prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Witter et al [8] stated that just to replace all teeth for rehabilitation purposes is not clinically proficient since SDA fulfills all of the requirements for satisfactory functional occlusion, provides sufficient oral comfort in terms of chewing ability and dental appearance, has sufficient mandibular stability to prevent signs and symptoms of mandibular dysfunction, and is thus a healthy stomatognatic system, and both the dentist and patient should choose it wisely. Basic knowledge of SDA is important for all dentists, so they can consider a simpler treatment plan for selected patients, if applicable, rather than trying to restore the occlusion of the whole dental arch, which is more complex, timeconsuming, and expensive [32].…”
Section: Discussionmentioning
confidence: 99%
“…The 40.3% response rate was in accordance with and, in some cases, higher than the response rates of other similar studies conducted on SDA in the UK (42%) and Australia (40.3%) [ 14 , 20 ], however, it is considered lower than other studies conducted in KSA, Malaysia, and Jordan, which had response rates of 72.1%, 84%, and 70.7%, respectively [ 15 , 21 , 22 ]. The low response rate could be due to the usage of an online survey distributed via e-mail, as electronic surveys have lower response rates than physical ones [ 23 ].…”
Section: Discussionsupporting
confidence: 84%